2011
DOI: 10.1152/ajpendo.00538.2010
|View full text |Cite
|
Sign up to set email alerts
|

In vivo activation of ROCK1 by insulin is impaired in skeletal muscle of humans with type 2 diabetes

Abstract: To determine whether serine/threonine ROCK1 is activated by insulin in vivo in humans and whether impaired activation of ROCK1 could play a role in the pathogenesis of insulin resistance, we measured the activity of ROCK1 and the protein content of the Rho family in vastus lateralis muscle of lean, obese nondiabetic, and obese type 2 diabetic subjects. Biopsies were taken after an overnight fast and after a 3-h hyperinsulinemic euglycemic clamp. Insulin-stimulated GDR was reduced 38% in obese nondiabetic subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 41 publications
5
53
0
2
Order By: Relevance
“…Supporting this, in vitro studies with muscle cells also revealed that the ability of insulin to increase glucose transport was decreased when endogenous ROCK1 expression was inhibited (7). Furthermore, insulin stimulation of ROCK1 activity in skeletal muscle was significantly reduced in human subjects with obesity and type 2 diabetes, suggesting that impaired ROCK1 activation could contribute to the pathogenesis of insulin resistance in humans (8). However, experimental evidence from vasculature-related cell lines, including vascular smooth muscle cells, endothelial cells, and mammary epithelial cells, indicates that suppression of ROCK isoform activity with ROCK inhibitors fasudil or Y-27632 enhances insulin signaling by affecting IRS-1 tyrosine phosphorylation or PTEN (2,32,44,45).…”
mentioning
confidence: 83%
“…Supporting this, in vitro studies with muscle cells also revealed that the ability of insulin to increase glucose transport was decreased when endogenous ROCK1 expression was inhibited (7). Furthermore, insulin stimulation of ROCK1 activity in skeletal muscle was significantly reduced in human subjects with obesity and type 2 diabetes, suggesting that impaired ROCK1 activation could contribute to the pathogenesis of insulin resistance in humans (8). However, experimental evidence from vasculature-related cell lines, including vascular smooth muscle cells, endothelial cells, and mammary epithelial cells, indicates that suppression of ROCK isoform activity with ROCK inhibitors fasudil or Y-27632 enhances insulin signaling by affecting IRS-1 tyrosine phosphorylation or PTEN (2,32,44,45).…”
mentioning
confidence: 83%
“…Differing from previous studies, Chun et al indicated that RND3 can also bind to the kinase domain of ROCK1 and inhibit the catalytic activity of ROCK1. The effect of inhibition was notably increased in obese type 2 diabetic patients, accounting for defective ROCK1 activity (27). …”
Section: Interaction Of Rnd3 With Other Molecules/signalingmentioning
confidence: 99%
“…For chronic exposure experiments, HUVEC were treated with rIL-8 or CM from myotubes for 24 -72 h with or without anti IL-8-neutralizing antibodies (R & D Systems) or the phosphatidylinositol 3-kinase (PI3K) inhibitor LY-294002 (Sigma, St. Louis, MO) and then lysed in extraction buffer (7,38). Frozen muscle tissue was homogenized with a Polytron at half speed and lysed in extraction buffer, as described previously (6).…”
Section: Subjectsmentioning
confidence: 99%